MO736ELECTROCHEMICAL SKIN CONDUCTANCE BY SUDOSCAN: A NEW TOOL TO PREDICT INTRA-DIALYTIC HYPOTENSION. (29th May 2021) - Reach, Pauline; Touzot, Maxime; Lombardi, Yannis; Maheas, Catherine; Sacco, Emmanuelle; Fels, Audrey; Beaussier, Hélène; Urena Torres, Pablo Antonio; Chatelier, Gilles; Ridel, Christophe; Zuber, Mathieu
Abstract: Background and Aims: Intradialytic hypotension (IDH) is a common complication in hemodialysis (HD) patients. It is associated with multiple risk factors including cardiac dysfunction and alterations of the peripheral autonomic nervous system. To which extent, dysautonomia may contributed to the occurrence of IHD remains elusive. We sought to investigate the clinical utility of Sudocan®, a device that quantify dysautonomia, in the prediction of IDH. Method: We conducted a prospective monocentric study in adult HD patients from July 2019 to February 2020. Dysautonomia was assessed by the measurements of hand and foot Electrochemical Skin Conductance (ESC) by Sudocan®, before and after the end of HD. A pathological hand ESC was defined by an ESC value < 40 μs in Caucasian or < 30 μs in afro-American and Caribbean patients, and a pathological foot ESC by a value < 50 μs in Caucasian or < 30 μs in afro-American and Caribbean patients. Arterial blood pressure (BP) was monitored before, every thirty minutes and after the end of the HD session. The primary end point was the incidence of IDH, according to the NKD/K-DOQI definition, during the 3 month-period study. Results: A total of 176 HD patients (64 ±14 years old) were enrolled. Mean pre-dialysis hand and foot ESC were 45±20 μS and 54±22 μS, respectively. Thirty-five and 40% of patients had a pathological ESC at the hand and foot, respectively. Forty-Six IDH occurred during the study period. Logistic regression showed that a pathological hand ESC was associated with an increased risk of IDH [OR=0.39, IC95% (0.15-0.97), p= 0.04]. The cumulative risk incidence of IHD during the study was 2.17 [IC95% (1.21-3.89), p= 0.01] and 1.89 [IC95% (1.06-2.38), p= 0.03], with a pathological hand and foot ESC, respectively. Conclusion: A pathological hand ESC, as assessed by a simple, non-invasive test, such as Sudoscan®, is associated with an increased risk of IDH.